2020
DOI: 10.1177/1938640020916954
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Nonoperative Functional Protocols for Acute Achilles Ruptures Utilizing a Formal Rehabilitation Protocol Showing Lowest Rerupture Rates

Abstract: Aim. To lay out a comprehensive protocol for practitioners and physical therapists that has the lowest rerupture rates for nonoperative treatment of acute Achilles ruptures. Method. Relevant articles were searched in PubMed, CINAHL Plus, and Cochrane Library using keyword combinations: nonoperative AND/OR Achilles rupture AND functional AND/OR protocol or functional AND/OR rehabilitation. To be included in the full analysis, the studies had to have detailed functional protocols with physical therapy program de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 31 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…The concerns rose in the past referred to the risk of re-rupture following a functional rehabilitation protocol have been overcome due to new data that support it, which showed lower re-rupture rates when compared with non-weightbearing and casting [ 70 , 71 , 75 ]. The lowest re-rupture rates were found in strict functional rehabilitation protocols with full weightbearing in boot immediately at full equinus or at 30° of plantar flexion [ 76 ].…”
Section: Principles Of Rehabilitationmentioning
confidence: 99%
“…The concerns rose in the past referred to the risk of re-rupture following a functional rehabilitation protocol have been overcome due to new data that support it, which showed lower re-rupture rates when compared with non-weightbearing and casting [ 70 , 71 , 75 ]. The lowest re-rupture rates were found in strict functional rehabilitation protocols with full weightbearing in boot immediately at full equinus or at 30° of plantar flexion [ 76 ].…”
Section: Principles Of Rehabilitationmentioning
confidence: 99%
“…The total duration of orthosis use varies considerably, with most studies recommending a brace for 8 weeks. 27,34,38,39 Aujla et al 39 did not find any significant increase in complications when their protocol was modified to decrease the time in the brace from 11 weeks to 8 weeks. In a recent systematic review, removal of the orthosis before 8 weeks demonstrated significantly higher rerupture rates, higher Achilles tendon rupture scores, and lower rates of return to work, but no effect on rates of Deep vein thrombosis or return to sport.…”
Section: Duration Of Bracingmentioning
confidence: 91%
“…A tendon gap of 5 mm and 10 mm has been proposed as the cutoff for higher and lower-demand patients, respectively. [26][27][28][29] Some studies have used a 5 mm gap as an absolute cutoff for nonoperative management. 27,30 Other authors have concluded any gap in full equinus is a contraindication to nonoperative management.…”
Section: Gap Sizementioning
confidence: 99%
See 2 more Smart Citations